2020
DOI: 10.1186/s13020-020-00347-5
|View full text |Cite
|
Sign up to set email alerts
|

An effective UFLC–MS/MS method used to study pharmacokinetics of major constituents of Fukeqianjin formula in rat plasma

Abstract: Background: Fukeqianjin formula (FKQJF) is a Chinese medicine prescription, which has been widely used individually or in combination with other western medicine for the treatment of various gynecological inflammatory diseases, including chronic cervicitis, chronic pelvic inflammatory disease and endometritis, so on and so force. Methods: The ultra-fast liquid chromatography coupled with triple quadrupole tandem mass spectrometry (UFLC-MS/MS), a quick and efficient method was established and applied to quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“… Dangshen Roots of C. pilosula To promote Qi. immunoregulation [ 9 ] Fukeqianjin formula (FKQJF) 8 Plant ingredients including roots of C. pilosula Treatment of gynecological inflammatory diseases (chronic cervicitis, chronic pelvic inflammatory disease, endometritis) [ 113 115 ] Fufang E’jiao Jiang (FEJ) TCM derived from “Liangyi Ointment”. Mixture of 5 plants including C. pilosula Medication against weakness and anemia (used to treat chemotherapy-induced myelosuppression) [ 116 118 ] Shenqi Fuzheng injection (SFI) Extract made from Radix Astragali and Radix Codonopsis Treatment of chronic heart failure.…”
Section: Introductionmentioning
confidence: 99%
“… Dangshen Roots of C. pilosula To promote Qi. immunoregulation [ 9 ] Fukeqianjin formula (FKQJF) 8 Plant ingredients including roots of C. pilosula Treatment of gynecological inflammatory diseases (chronic cervicitis, chronic pelvic inflammatory disease, endometritis) [ 113 115 ] Fufang E’jiao Jiang (FEJ) TCM derived from “Liangyi Ointment”. Mixture of 5 plants including C. pilosula Medication against weakness and anemia (used to treat chemotherapy-induced myelosuppression) [ 116 118 ] Shenqi Fuzheng injection (SFI) Extract made from Radix Astragali and Radix Codonopsis Treatment of chronic heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of compound chemical components research of GZD, we studied the major effective compounds observed in blood through the pharmacokinetics research, which were the mostly possible material basis of GZD [27]. Moreover, the research help to clarify the biologically active ingredients and mechanism of action in TCM prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this clinical trial was aimed to evaluate the efficacy and safety of FUKE capsules in female Pakistani patients with mild-to-moderate PID symptoms. (Wang et al, 2020). FUKE is a Chinese patent medicine (CN1251763A).…”
Section: Introductionmentioning
confidence: 99%
“…FUKE is a Chinese patent medicine (CN1251763A). Its composition and the processes of extraction and preparation are reported in this patent and described by Wang et al (2020), and its chemical fingerprint is reported by Ma et al (2021).…”
Section: Introductionmentioning
confidence: 99%